2009
DOI: 10.1007/s00421-009-1223-2
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of 2H2O in plasma and eccrine sweat during exercise-heat stress

Abstract: The purpose of this research was to characterize the movement of ingested water through body fluids, during exercise-heat stress. Deuterium oxide ((2)H(2)O) accumulation in plasma and eccrine sweat was measured at two sites (back and forehead). The exercise of 14 males was controlled via cycle ergometry in a warm environment (60 min; 28.7 degrees C, 51%rh). Subjects consumed (2)H(2)O (0.15 mg kg(-1), 99.9% purity) mixed in flavored, non-caloric, colored water before exercise, then consumed 3.0 ml kg(-1) contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…Because the eccrine sweat gland draws fluid from the interstitial compartment, perhaps the appearance of D 2 O in the plasma or serum may be used as an index of fluid bioavailability to the eccrine sweat gland when a person is not actively sweating. Although the fluid would be transported from the duct to the secretory coil before it is secreted onto the skin, it appears that this process may occur within a few minutes (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the eccrine sweat gland draws fluid from the interstitial compartment, perhaps the appearance of D 2 O in the plasma or serum may be used as an index of fluid bioavailability to the eccrine sweat gland when a person is not actively sweating. Although the fluid would be transported from the duct to the secretory coil before it is secreted onto the skin, it appears that this process may occur within a few minutes (3).…”
Section: Discussionmentioning
confidence: 99%
“…Armstrong et al (3) found that water ingested orally during exercise appears in sweat in as early as 10 minutes. We hypothesize that D 2 O will not appear in the sweat as quickly when an athlete is dehydrated and at rest during recovery from exercise in the heat but may be apparent within the first 20 minutes.…”
Section: Introductionmentioning
confidence: 98%
“…Using previously published time estimates for fluid movement through various tissues in the body, we estimated that the minimum time duration required for ingested fluid to appear as sweat to be approximately three minutes. This is considerably less than the 10 min period currently reported in the literature (Armstrong, et al, 2010). Therefore, the purpose of this study was to test our theorized time estimate for water movement by identifying the initial enrichment of D 2 O in eccrine sweat following fluid ingestion during continuous exercise in the heat.…”
Section: Introductionmentioning
confidence: 97%
“…Only three studies (Armstrong, et al, 2010;Davis et al, 1985;Koulmann, et al, 1997) in the scientific literature have addressed this topic, and none were specifically designed to determine how rapidly ingested water starts to appear as sweat. For example, the seminal study by Armstrong et al (2010) determined fluid kinetics from ingestion to sweat secretion using deuterium oxide (D 2 O) enrichment during an hour of exercise in the heat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation